Smoking behaviour modifies IL23r‐associated disease risk in patients with Crohn's disease. Issue 2 (February 2015) - Doecke, James D; Simms, Lisa A; Zhao, Zhen Zhen; Roberts, Rebecca L; Fowler, Elizabeth V; Croft, Anthony; Lin, Angela; Huang, Ning; Whiteman, David C; Florin, Timothy H J; Barclay, Murray L; Merriman, Tony R; et al.
Abstract Background and Aim The etiology of Crohn's disease (CD) implicates both genetic and environmental factors. Smoking behavior is one environmental risk factor to play a role in the development of CD. The study aimed to assess the contribution of the interleukin 23 receptor (IL23R) in determining disease susceptibility in two independent cohorts of CD, and to investigate the interactions between IL23R variants, smoking behavior, and CD‐associated genes, NOD2 and ATG16L1. Methods Ten IL23R single‐nucleotide polymorphisms (SNPs) were genotyped in 675 CD cases, and 1255 controls from Brisbane, Australia (dataset 1). Six of these SNPs were genotyped in 318 CD cases and 533 controls from Canterbury, New Zealand (dataset 2). Case–control analysis of genotype and allele frequencies, and haplotype analysis for all SNPs was conducted. Results We demonstrate a strong increased CD risk for smokers in both datasets (odds ratio 3.77, 95% confidence interval 2.88–4.94), and an additive interaction between IL23R SNPs and cigarette smoking. Ileal involvement was a consistent marker of strong SNP–CD association (P ≤ 0.001), while the lowest minor allele frequencies for location were found in those with colonic CD (L2). Three haplotype blocks were identified across the 10 IL23R SNPs conferring different risk of CD. Haplotypes conferred no further risk of CD when compared with single SNP analyses. Conclusion IL23R gene variants determine CD susceptibility in the Australian and New Zealand population, particularly ileal CD. A strong additive interaction exists between IL23R SNPs and smoking behavior resulting in a dramatic increase in disease risk depending upon specific genetic background.